Sosialisasi Gerakan Literasi Dini Kepada Guru TK dan PAUD Makanatut Thalibin di Kecamatan Aluh-aluh - Akhmad Syakir; M Ridha Anwari; Muhammad Yunus (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2019)
ABSTRACT: Community service is aimed to socialize the early literacy movement for teachers and parents of PAUD I students in Pulantan Village, Aluh-Aluh District. This dedication was held on Thursday, March 22, 2018 in PAUD Makanatut Thalibin. The target of this activity is PAUD teachers and parents of students. The reason for implementing this service is a school that is far from the city center, a low level of education from parents of students so that the planting of early literacy to their children is often unthinkable to them, even the planting of early literacy they submit to school. The method in this socialization uses the lecture method, discussion and question and answer, to provide knowledge on the importance of early literacy in children. After this implementation it can be concluded that the awareness of students' parents the importance of instilling a culture of early literacy for children, while for PAUD teachers Makanatut Thalibin they understand that many methods of teaching early literacy are fun for students.